Operation of braced steel frameworks with regard to assembly and fabrication errors - Youssef R. Hamaty; Alexander R. Tusnin (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. As a building construction material, steel is widely used because of its high mechanical characteristics. Steel load-bearing structures of multi-storey buildings are a system formed by columns, beams, floor slabs and braces. The frame of a multi-storey building has a large number of elements and their connections. Errors in the fabrication, installation and operation of steel frames of multi-storey buildings can lead to a reduction in the load-bearing capacity of structures compared to the design. Deviations from the design position occur because of violations of the technical operatin.rules of the buildings beyond the permissible limits, design errors, imperfect standards and poor quality of work during the fabrication and installation of structures. The current Russian standards do not take into account the impact of fabrication and installation errors on the work of multi-storey frames. The initial geometric defects in the structural system and its individual elements contribute to the difference in performance between the real construction and an idealized one.Materials and methods. The study of the effect of initial imperfections on the stress-strain state of the steel frame is important and relevant. Initial imperfections are taken into account either by applying an equivalent load to the idealized design scheme or by forming a geometrically distorted by imperfections design scheme. The analysis can be linear or geometrically non-linear.Results. The results of the study of braced steel framework performance in the presence of initial imperfections are presented. The effect of initial imperfections in the form of deflection of columns from the vertical is considered. The values of the initial imperfections are determined in accordance with the current RF standards.Conclusions. The results obtained have made it possible to propose a correction factor to the results of the calculation of frames with imperfections to the results of the calculation of an idealized frame.